Merī bihtarīn naẓm : ḵẖvud shuʻarā kī muntaḵẖab naẓmoṉ kā majmūʻah - ʻAskarī, Muḥammad Ḥasan, 1921-1978 (SAMP early 20th-century Indian books project ;, 1942)
Anthology of Urdu poetry; includes biographical notes on the poets.